5x+4-3x=7x-8+11

Simple and best practice solution for 5x+4-3x=7x-8+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+4-3x=7x-8+11 equation:


Simplifying
5x + 4 + -3x = 7x + -8 + 11

Reorder the terms:
4 + 5x + -3x = 7x + -8 + 11

Combine like terms: 5x + -3x = 2x
4 + 2x = 7x + -8 + 11

Reorder the terms:
4 + 2x = -8 + 11 + 7x

Combine like terms: -8 + 11 = 3
4 + 2x = 3 + 7x

Solving
4 + 2x = 3 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
4 + 2x + -7x = 3 + 7x + -7x

Combine like terms: 2x + -7x = -5x
4 + -5x = 3 + 7x + -7x

Combine like terms: 7x + -7x = 0
4 + -5x = 3 + 0
4 + -5x = 3

Add '-4' to each side of the equation.
4 + -4 + -5x = 3 + -4

Combine like terms: 4 + -4 = 0
0 + -5x = 3 + -4
-5x = 3 + -4

Combine like terms: 3 + -4 = -1
-5x = -1

Divide each side by '-5'.
x = 0.2

Simplifying
x = 0.2

See similar equations:

| y-2=1/2(x-(-4)) | | 218-178= | | 6x^3+15X^2+6x=0 | | 46.37*18.48= | | 2xy*x+3y= | | 6(x^2)+6x-44=0 | | 5(2x-6)=2(5-x) | | 3+4=-5+2 | | 3x+2=-5x+4 | | 4*(3+4x)=-18 | | 12d+7=6d+31 | | 13x+15-(x+2)= | | 5(a+7)=38 | | 47.2=9c-5 | | y=kx+10 | | 4e-7=9 | | 7p=21.7 | | 3x^2-16=2-3x | | 7e-9=26 | | 10q-5q+17-9= | | 7h+8g+2h+g= | | y=2(x+1) | | .11x+.08(165000-x)=15750 | | .11x+.08x(165000-x)=15750 | | (4x+3)+(3x+2)= | | h=-0.005t^2+0.6t+2 | | h=-0.005x^2+0.6t+2 | | h=0.005t^2+0.6t+2 | | 3x+1+3x+6= | | 8n+(5n+13)=7 | | 9x^3-105x^2-56x=0 | | 3x^3+170x^2-57x=0 |

Equations solver categories